Care-'less': exploring the interface between child care and parental control in the context of child rights for workers in children's homes in Ghana - Ernest Darkwah; Marguerite Daniel; Joana Salifu Yendork (BMC, 2018)
Abstract Background This study explored how employed caregivers experience the interface between child care, parental control and child rights in the context of Children's Homes in Ghana. The focus was on investigating caregiver perceptions of proper child care, their experiences with having to work with child rights principles and the implication of these for their relationships with the children and the care services they deliver. Methods Adopting a qualitative approach with phenomenological design, data were collected from 41 caregivers in two children's homes in Ghana using focus group discussions and in-depth interviews. Results It emerged that caregivers experienced frustrations with perceived limitations that child rights principles place on their control over the children describing it as lessening and, at the same time, complicating the care services they provide. Conclusions The findings suggest a need for a review of the implementation strategies of the child rights approach in that context. A re-organization of the children's homes environment and re-orientation of caregivers and children regarding their relationship is also suggested.